Identification and outcomes of acute kidney disease in patients presenting in Bolivia, Brazil, South Africa, and Nepal. - Rhys D R Evans; Sanjib K Sharma; Rolando Claure-Del Granado; Brett Cullis; Emmanuel A Burdmann; Fos Franca; Junio Aguiar; Martyn Fredlund; Kelly Hendricks; Maria F Iturricha-Caceres; Mamit Rai; Bhupendra Shah; et al. (PLoS Medicine)
Background The International Society of Nephrology proposes an acute kidney disease (AKD) management strategy that includes a risk score to aid AKD identification in low- and low-middle-income countries (LLMICs). We investigated the performance of the risk score and determined kidney and patient outcomes from AKD at multiple LLMIC sites. Methods and findings Adult patients presenting to healthcare facilities in Bolivia, Brazil, South Africa, and Nepal were screened using a symptom-based risk score and clinical judgment. Those at AKD risk underwent serum creatinine testing, predominantly with a point-of-care (POC) device. Clinical data were collected prospectively between September 2018 and November 2020. We analyzed risk score performance and determined AKD outcomes at discharge and over follow-up of 90 days. A total of 4,311 patients were at increased risk of AKD, and 2,922 (67.8%) had AKD confirmed. AKD prevalence was 80.2% in patients enrolled based on the risk score and 32.5% when enrolled on clinical judgment alone (p < 0.0001). The area under the receiver operating characteristic curve was 0.73 for the risk score to detect AKD. Death during admission occurred in 84 (2.9%) patients with AKD and 3 (0.2%) patients without kidney disease (p < 0.0001). Death after discharge occurred in 206 (9.7%) AKD patients, and 1865 AKD patients underwent reassessment of kidney function after discharge; 902 (48.4%) patients had persistent kidney disease including 740 (39.7%) patients reclassified with de novo or previously undiagnosed chronic kidney disease (CKD). The study was pragmatically designed to assess outcomes as part of routine healthcare, and there was heterogeneity in clinical practice and outcomes between sites, in addition to selection bias during cohort identification. Conclusions The use of a risk score can aid AKD identification in LLMICs. High rates of persistent kidney disease and mortality after discharge highlight the importance of AKD follow-up in low-resource settings.